Multilevel surgery for obstructive sleep apnea: short-term results - Verse, Thomas; Baisch, Alexander; Maurer, Joachim T.; Stuck, Boris; Hörmann, Karl (Otolaryngology - head and neck surgery, 2006)
OBJECTIVE: To determine the efficacy of a new multilevel surgical protocol for obstructive sleep apnea (OSA)., STUDY DESIGN AND SETTING: Sixty patients with moderate to severe OSA because of multilevel pharyngeal obstruction were enrolled into this prospective, controlled clinical trial after clinical examination, endoscopy, and polysomnography. Surgery included uvulaflap, tonsillectomy, hyoid suspension, and radiofrequency treatment of the tongue base (group A). A second group did not receive hyoid suspension (group B). In both groups, nasal surgery was performed if necessary. Polysomnography and Epworth Sleepines Scale (ESS) were recorded at baseline and 2 to 15 months after surgery., RESULTS: In group A, the mean apnea-hypopnea index (AHI) decreased significantly after surgery (38.9 ± 20.0 vs 20.7 ± 20.6, P < 0.0001), whereas in group B the AHI did not. All secondary variables (minimal oxygen saturation, mean oxygen saturation, arousal index), and the ESS significantly improved in group A with only changes in arousal index and ESS reaching levels of significance in group B., CONCLUSION: The presented protocol including the hyoid suspension proved to be effective in the treatment of OSA, whereas surgery without hyoid suspension was less successful.